Folk Couplets against the Background of Historical Memory - Stundžienė, Bronė (Tautosakos darbai, 2022)
The article deals with a narrative emerging from the numerous corpus of the Lithuanian folk couplets, in order to highlight its connections with a certain background in the cultural memory, probably related to ancient mythical past, or a recent one associated to the so-called communication memory, which includes sharing recollections among people of the same or a couple of adjacent generations. The folk couplets are short rhymed folksongs, depicting comically or critically various phenomena, situations and human vices, and predominantly characterized by their acrimonious or obscene content. In their form and partly also in their content, these entertaining folksongs are rather close to the ritual folksongs performed at the weddings, or calendar festivals and other occasions. These kinds of folksongs are related in terms of the same artistic means – parody, humor, and irony, as well as of the content communicated by these means. They are also connected by their common denominations – lotinės dainos (‘barking songs’) or just lojimai (‘barking’), which associate singing with a dog’s bark. The mythical image of the dog and its bark is touched upon in the article too, tracing it back to pre-Christian beliefs. Wedding folksongs, or “barking”, have ritual meaning: namely, ensuring the new family’s fertility and thus – thriving of the entire community. The entertaining couplets have a much simpler function to perform: they are intended as merry-making at the parties and other communal gatherings, particularly among the young people, and are usually accompanied by music. Although, as proven by the folksong narrative emerging from these couplets that treat certain marginal social groups, such as beggars and the elderly, critically and even aggressively, the entertaining “barking songs” might serve as an important and publicly available instrument of “control over the social morality”. For instance, there are couplets mocking the so-called “fake beggars” that used to exist in virtually every Lithuanian parish of the 19th and the first half of the 20th century. These people would pretend to be lame and poor, gather at the churches and market squares during various religious festivities and scrounge for money and food. As often as not, the folk couplets aimed their typically aggressive mockery at the aged people (for instance, hundred-year-olds) and blamed them for living too long. Such cases may allude to the mythical notion of the old age: the hundred-year-olds allegedly use the vital energy of people who died too young.According to folklore researchers, humorous and playful folk couplets may only at first sight seem as mere entertainment. A special historical background turns them into an expression of social critique instead. This study draws on the printed and manuscript archived sources from the end of the 19th to the first half of the 20th century.
Keywords: folk couplet (Lith. talalinė); folk singing; barking; narrative; marginal group; historical memory